2016
DOI: 10.1177/0961203316655211
|View full text |Cite
|
Sign up to set email alerts
|

Dietary micronutrient intake and atherosclerosis in systemic lupus erythematosus

Abstract: SLE patients did not have different dietary micronutrient intake compared to controls. Phosphorus was associated with lupus activity. Riboflavin, phosphorus, selenium and thiamin were inversely associated with atherosclerotic plaque, left side in SLE patients, but not in controls. Dietary micronutrients may play a role in atherosclerosis in SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…To this aim, biomarkers can be a superior method to determine Se nutritional status. 20 Our data show that jSLE patients had highly variable cumulative doses of corticosteroids; half of included patients were on corticosteroids upon enrollment. The excessive use of corticosteroids leads to an increase in gluconeogenesis and impairs insulin sensitivity, leading to abnormalities in carbohydrate metabolism.…”
Section: Discussionmentioning
confidence: 69%
“…To this aim, biomarkers can be a superior method to determine Se nutritional status. 20 Our data show that jSLE patients had highly variable cumulative doses of corticosteroids; half of included patients were on corticosteroids upon enrollment. The excessive use of corticosteroids leads to an increase in gluconeogenesis and impairs insulin sensitivity, leading to abnormalities in carbohydrate metabolism.…”
Section: Discussionmentioning
confidence: 69%
“…To date, there are no studies in the literature in the SLE population reporting similar results, possibly owing to the diversity of methodologies, although a study demonstrated that a dietary folic acid deficiency in SLE may be associated with atherosclerosis 19 , which in the present study was associated with MR. High micronutrient intake was reported as protective against excess weight in the Mexican SLE population 14 .…”
Section: Discussionmentioning
confidence: 54%
“…In another study, low fruit and vegetable consumption and insufficient dietary calcium and iron intake were observed 15 . The literature reports low micronutrient intake in patients with SLE and its possible association with atherosclerosis in this population 19 . The present study found an association of insufficient intake of some micronutrients with MR; i.e., an insufficient intake of folic acid (vitamin B9), choline, and sulfur was associated with the grouping of anthropometric indicators for obesity.…”
Section: Discussionmentioning
confidence: 80%
“…With the inclusion of walnuts in the diets of our participants, the dietary intake of carbohydrate, sugar, fiber, potassium, sodium, riboflavin, niacin, vitamin B 6 , folic acid, vitamin B 12 , vitamin A, and cholesterol did not show any meaningful changes. According to previous studies, [34][35][36][37][38][39] increased dietary intake of potassium, fiber, riboflavin, niacin, vitamin B 6 , folic acid, vitamin B 12 , and vitamin A has been associated with reduced cardiometabolic risk factors. The increased dietary intake of carbohydrate, sugar, sodium, and cholesterol has been associated with increased cardiometabolic risk factors.…”
Section: Discussionmentioning
confidence: 99%